Conformer-selective Photodynamics of TrpH+−H2O - Molina, Franco Leonardo (2023)
The photodynamics of protonated tryptophan and its mono hydrated complex TrpH+−H2O has been revisited. A combination of steady-state IR and UV cryogenic ion spectroscopies with picosecond pump-probe photodissociation experiments sheds new lights on the deactivation processes of TrpH+ and conformer-selected TrpH+−H2O complex, supported by quantum chemistry calculations at the DFT and coupled-cluster levels for the ground and excited states, respectively. TrpH+ excited at the band origin exhibits a transient of less than 100 ps, assigned to the lifetime of the excited state proton transfer (ESPT) structure. The two experimentally observed conformers of TrpH+−H2O have been assigned. A striking result arises from the conformer-selective photodynamics of TrpH+−H2O, in which a single water molecule inserted in between the ammonium and the indole ring hinders the barrierless ESPT reaction responsible for the ultra-fast deactivation process observed in the other conformer and in bare TrpH+.